(untitled) (Vietnam Journal of Community Medicine, 2024)
Introduction: Nutritional care in hospitals plays a positive role in patient outcomes and treatment costs. To effectively implement dietary and nutritional care in hospitals, one of the five main inputs is human resources. This research aims to provide scientific evidence for managers to develop suitable solutions and plans to enhance the professional capacity of healthcare staff in patient nutritional care, thereby contributing to the improvement of hospital quality. Objective: To describe the current state of healthcare staff’ knowledge about patient nutritional care at Thu Duc City Hospital in 2024. Methods: The study was conducted at Thu Duc City Hospital from February 2024 to September 2024. It used a cross-sectional quantitative research method, interviewing 337 healthcare staffs directly involved in patient care at the hospital. Conclusion: The level of knowledge achieved regarding nutritional care among healthcare staff is 60.5%. In specific knowledge areas, the achieved percentage is not high: knowledge achieved about nutrition and malnutrition of patients: 67.4%; knowledge achieved about screening and assessing nutritional status: 60.5%; knowledge achieved about providing nutritional support for patients: 62.6%; knowledge achieved about hospital diet: 45.1%; knowledge achieved about the tasks of nutritional care for patients: 66.2%. The knowledge of proper care classification has a higher rate among doctors compared to nurses (49.2% vs. 44.1%).